PENGARUH DEBT TO EQUITY RATIO (DER), PENGARUH DEBT TO EQUITY RATIO (DER), DAN RETURN ON ASSET (ROA) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Lili Syafitri; Ferny Irmarety (Jurnal RATRI (Riset Akuntansi Tridinanti), 2019)
ABSTRACT               The purpose of this study was to determine how much influence the Debt to Equity Ratio (DER), Return on Equity (ROE), and Return on Assets (ROA) as independent variables together on Stock Return as a dependent variable in Manufacturing Companies in the Industrial Sector Consumption Listed on the Indonesia Stock Exchange.               The research method used is descriptive analysis research. To obtain the data needed for this writing, the writing uses data collection activities by means of documentation, and literature study. The data that has been collected is then analyzed based on the associative descriptive analysis method. Data processing in this study was assisted by the Statistical For Product and Service Solution (SPSS) program version 23. The design used in this study used an associative method, namely research that aims to determine the effect or relationship between two or more variables.               The results of this study stated that simultaneous and partial Debt to Equity Ratio (DER), Return on Equity (ROE), and Return on Assets (ROA) had no significant effect on Stock Return.Keywords: Debt to Equity Ratio (DER), Return on Equity (ROE), Return on Assets (ROA), and Stock Return